Sifat Mekanik Komposit Sandwich Berpenguat Serat BambuFiberglass dengan Core Polyurethane Rigid Foam - Catur, Agus Dwi; D.S., Paryanto; Sinarep, Sinarep; Prayitno, Nanang (Jurnal Rekayasa Mesin, 2014)
Strong and rigid material is needed to restrain the bending load. Sandwich construction is applied when the stiff light material is needed. Fiberglass is a high strength fibers, while the bamboo fiber is a strong natural fiber. Both of these fiber reinforce composite resin. Compressive strength, bending strength and specific gravity of sandwich composites were discussed in this paper. Composite sandwich with fiberglass-bamboo fiber reinforcement and with a polyurethane rigid foam core sheet 25 mm have been manufactured and tested. Composite sandwich made by two laminated skin and a core. The number of layers fiber and type of composite sandwich were varieted in this study. There was no striking difference in the value of compressive strength of sandwich composite with variations of amount reinforcement layers of the skin. The compressive strength on edge area showed that the number and the type of layer on the skin will determine compressive strength. The compressive strength on the edge area will increase by increasing the number of layers. Bamboo lamina gives a better compressive strength than the fiberglass lamina. Sandwich composite density was lower than the average density of wood, it was ranged from 97.1 to 392.1 kg/m . The bending test was conducted by using four-point bending to determine the bending strength. The highest bending strength of the composite was obtained at 798 N/cm 3 . This value is owned by composite variants with skin consists of two layers of woven bamboo combined with 1 layer of fiberglass.Keywords: sandwich composite, bamboo, specific gravity, bending, polyurethane.